Five essential Interactive methods to boost speaking in English lesson (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Enhancing students' speaking skills in English is crucial for their overall language proficiency and confidence. This guide presents effective strategies to boost oral communication in the classroom, along with five interactive activities designed to engage students and promote speaking practice. By incorporating these activities, educators can create a dynamic learning environment that encourages students to express themselves freely and confidently